Synergistic effect of avidin/biotin system with biofunctionalized graphene oxide based nanocarrier in targeted co‐delivery of hydrophobic anticancer drug SN‐38. Issue 3 (31st January 2022) - Karki, Neha; Tiwari, Himani; Matiyani, Monika; Bal, Rajaram; Pal, Mintu; Sahoo, Nanda Gopal
Abstract: Co‐delivery of chemotherapeutic drugs with protein (avidin) within a solitary nanocarrier system has emerged as a promising combination therapy approach for treating cancers owing to their synergistic effect. In this study, we developed a potential nanocarrier by using graphene oxide (GO), activated folic acid (FA), polyethylene glycol (PEG), and TiO2 nanoparticles. PEG was introduced to enhance the nanocarrier's water solubility and biocompatibility. Further the synthesized primary nanocarrier that is, GO–FA–PEG–TiO2 employed with avidin‐biotin (Avi/Bio) system and synthesized more efficient nanocarrier that is, GO–FA–PEG–TiO2 –Avi/Bio to enhance potential anti‐tumor activity and targeted co‐delivery of anticancer drug, SN‐38. The morphological analysis of nanocarrier GO–FA–PEG–TiO2 –Avi/Bio was confirmed by basic characterization techniques including RAMAN, Fourier transforms infrared, Thermo gravimetric Analyzer, and Field Emission Scanning Electron Microscopy. The loading capacity of SN‐38 revealed that the nanocarrier integrated with Avi/Bio complex possessed higher adsorption capability than nanocarrier without Avi/Bio system. Furthermore, GO–FA–PEG–TiO2 –Avi/Bio showed pH‐responsive behavior of releasing SN‐38. In‐vitro experiments confirmed sustained release of the drug, with a better performance at physiological pH (7.4) than at acidic pH (5.0). The developed nanocarrier with Avi/Bio complex showed higher cytotoxic effects than the GO–FA–PEG–TiO2 system. The cytotoxicity screening of GO–FA–PEG–TiO2 –SN‐38 and GO–FA–PEG–TiO2 –Avi/Bio–SN‐38 was conducted with MDA‐MB‐231 cells. Thus, GO–FA–PEG–TiO2 –Avi/Bio system, when used as nanocarriers, showed high payload capacity to target cancer cells with increased cytotoxicity. Abstract : In the present work, comparative study was carried out to evaluate the drug loading capacity, release behavior, and cytotoxic activity of SN‐38 incorporated with the GO–FA–PEG–TiO2 and GO–FA–PEG–TiO2 –Avi/Bio.